THE ROLE OF ARTIFICIAL INTELLIGENCE IN DETECTING DIGITAL CRIMES - Yunusova Minavvarkhon Sabirovna Sabirovna (PT. Antis International Publisher, 2025)
Objective: This study aims to investigate the role of artificial intelligence (AI) in detecting and preventing digital crimes, with a particular focus on adapting global practices to the Uzbek context. Method: A comparative analysis was conducted, drawing on case studies from the USA, UK, Singapore, Japan, and Estonia, alongside an assessment of Uzbekistan’s cybercrime dynamics between 2020 and 2024. The study evaluated AI applications such as machine learning, natural language processing, anomaly detection, and biometric systems, and examined their relevance to Uzbekistan’s infrastructure, regulatory framework, and expertise. Results: Findings indicate that AI technologies enhance detection accuracy by 30–50% compared to human-led methods, providing significant improvements in real-time monitoring, fraud prevention, and predictive analysis. Despite the presence of legal measures, Uzbekistan continues to face technical and organizational challenges that limit effective crime prevention. Novelty: This research contributes by linking international best practices with national needs, demonstrating AI’s potential as an “active assistant” in law enforcement. It underscores the importance of integrating AI adoption with legal reforms, professional training, and public–private collaboration to strengthen digital security and support the sustainable growth of Uzbekistan’s digital economy.